2001
DOI: 10.1056/nejm200101113440201
|View full text |Cite
|
Sign up to set email alerts
|

Cellular-Telephone Use and Brain Tumors

Abstract: These data do not support the hypothesis that the recent use of hand-held cellular telephones causes brain tumors, but they are not sufficient to evaluate the risks among long-term, heavy users and for potentially long induction periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
270
4
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(291 citation statements)
references
References 30 publications
11
270
4
6
Order By: Relevance
“…To date, several case -control studies have been reported from the United States (Muscat et al, 2000;Inskip et al, 2001), Finland (Auvinen et al, 2002), and Sweden (Hardell et al, 1999(Hardell et al, , 2002(Hardell et al, , 2003(Hardell et al, , 2004 before the INTERPHONE study. Two US studies showed negative results for the overall risk of brain tumours, whereas in a Finnish population register-based study, the OR for glioma with relation to ever use of analogue mobile phones was 2.1 (95% CI: 1.3 -3.4).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several case -control studies have been reported from the United States (Muscat et al, 2000;Inskip et al, 2001), Finland (Auvinen et al, 2002), and Sweden (Hardell et al, 1999(Hardell et al, , 2002(Hardell et al, , 2003(Hardell et al, , 2004 before the INTERPHONE study. Two US studies showed negative results for the overall risk of brain tumours, whereas in a Finnish population register-based study, the OR for glioma with relation to ever use of analogue mobile phones was 2.1 (95% CI: 1.3 -3.4).…”
Section: Discussionmentioning
confidence: 99%
“…5,16 There is no evidence supporting the influence of mobile phone use on the occurrence of benign or malignant CNS tumors, especially those located in the temporal lobe. 17,18,24 Results of studies on mobile phone handset radiation and the risk of developing acoustic neuroma have been contradictory (Table 1). Some authors have found no increased probability of tumor development in mobile phone users, 18,19,21,24 while other have stated that the use of mobile phones -particularly analog handsets -for 10 years or more is a risk factor for developing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,24 Results of studies on mobile phone handset radiation and the risk of developing acoustic neuroma have been contradictory (Table 1). Some authors have found no increased probability of tumor development in mobile phone users, 18,19,21,24 while other have stated that the use of mobile phones -particularly analog handsets -for 10 years or more is a risk factor for developing tumors. 7,20,23 Muscat et al (2002) 19 have pointed out that acoustic neuromas are slow-growing tumors, and may have been present in case-control study subjects before they began to use mobile phones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have failed to reveal a link between brain cancer and use of cellular telephones (Muscat et al, 2000;Inskip et al, 2001;Johansen et al, 2001), although there were limitations in terms of the duration of phone use and length of follow-up. A recently published case -control interview study from Germany reported a significant four-fold increased risk of malignant melanoma of the eye associated with the use of radiofrequency (RF) transmitting devices, including mobile telephones (Stang et al, 2001).…”
mentioning
confidence: 99%